دراسة أوليـة للجرعات الإشعاعية للمرضى الناشئة عن فحوص الأشعة السينية التشخيصية - يوسف ابويكر عبدالله; البقي اسامة مهدى; اهويدي زيدان ضو (The Libyan Journal of Science, 2022)
Substantial change in radiation doses to patients for the same diagnostic radiology is revealed in many studies dealing with radiation surveys. Establishing reference dose levels is also a key factor in the process of reducing these changes. This study aims to measure the absorbed radiation dose "Entrance Surface Dose ESD" using TLD -100 for four tests: cervical spine, foot, wrist and elbow. The results of this study indicate that the ESD for Elbow AP projection is 0.34 mGy and LAT projection is 0.26 mGy, Foot AP is 0.24 mGy, LAT is 0.22 mGy, wrist AP is 0.22 mGy, LAT is 0.29 mGy, and the cervical spine LAT is 1.67 mGy. Thus this study emphasizes the importance of quality assurance program in hospitals and other centers which deal with diagnostic radiology and develop local diagnostic reference level.